Technology Integration Performance Assessment Using Lean Principles in Health Care. (July 2015) - Rico, Florentino; Yalcin, Ali; Eikman, Edward A.
This study assesses the impact of an automated infusion system (AIS) integration at a positron emission tomography (PET) center based on "lean thinking" principles. The authors propose a systematic measurement system that evaluates improvement in terms of the "8 wastes." This adaptation to the health care context consisted of performance measurement before and after integration of AIS in terms of time, utilization of resources, amount of materials wasted/saved, system variability, distances traveled, and worker strain. The authors' observations indicate that AIS stands to be very effective in a busy PET department, such as the one in Moffitt Cancer Center, owing to its accuracy, pace, and reliability, especially after the necessary adjustments are made to reduce or eliminate the source of errors. This integration must be accompanied by a process reengineering exercise to realize the full potential of AIS in reducing waste and improving patient care and worker satisfaction.